FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT PEMBELIAN ULANG PONSEL PINTAR DI KALANGAN MAHASISWA - Nadhira, Ratna; Hartono, Arif (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
Smartphones are considered by students as a tool to encourage interaction, multitasking, and learning, in addition, students regularly use smartphones as a tool for e-learning and web-based education, where the advantages of owning a smartphone can include increased productivity, information retrieval, information and social interaction, relaxation, and entertainment. This study aims to examine the repurchase intention of students on the smartphone brand they use. This research was conducted on 132 respondents who are students who use smart phones every day and have at least replaced their smart phones more than once. This study uses primary data and convenience sampling technique in sampling. The analysis test was carried out using the Structural Equation Model based on Partial Least Square and processing the data using the Smart PLS program. The results of the data analysis test showed that the five hypotheses were significant. (1) Brand awareness has a positive effect on brand loyalty, (2) Perceived quality has a positive effect on brand loyalty, (3) Brand loyalty has a positive effect on repurchase intention, (4) Brand Personality has a positive effect on brand preference, (5) Preference Brand has a positive effect on repurchase intention